(untitled) (International Journal of Ayurveda and Pharma Research, 2025)
Rasashastra is the Iatrochemistry of Ayurveda which deals with the various pharmaceutical processes of Shodhana (purification/potentiation), Marana (incineration/calcination), Jarana (polling) and other detailed descriptions of metals, minerals, poisonous plants and animal products which are of therapeutic importance in Ayurveda. A series of pharmaceutical procedures that converts a metal/mineral into a therapeutically effective form is termed as Shodhana. Various methods along with different media are being used for the purification of metals/minerals. Failure to subject certain metals/minerals to the process of Shodhana can have a detrimental impact on the efficacy of the preparations. It is quite interesting to understand the role of media in the purification of Maharasa, Uprasa, Sadharna Rasa and Dhatu Varga.